Factionalism in Town and Countryside: The Significance of Puritanism and Arminianism - Fletcher, Anthony (Studies in church history, 1979)
Factionalism in the local communities of Stuart England is a many-sided subject which has hardly been investigated. I am concerned in this paper primarily widi die religious ingredient in local factionalism and in particular with a series of incidents of sustained hostility between clergy and laity, most of which occurred in the decade before the civil war. In every case conflict arose because clergymen were more or less assertively at odds either with deeply embedded custom and tradition or with strongly held views among the laity of their town or village. The intention is to consider die patterns of conflict that lie behind these incidents and to relate these patterns to the structures of rural and urban communities.